Thermal transmittance effect on energy consumption of Mediterranean buildings with different thermal mass - Rodrigues, Eugénio (2019)
High thermal mass construction is commonly used to reduce cooling energy consumption during the summer period as a passive design strategy in the Mediterranean region. Although being a generalized design practice, the benefit to the building performance is not fully consensual within the scientific community. This work explores the influence of thermal transmittance on the energy efficiency of buildings with different thermal mass levels. Hence, a statistical comparison of the buildings’ annual energy consumption for air-conditioning is carried out based on two synthetic datasets with high and low thermal mass and varying thermal transmittance for opaque and transparent elements. In addition to climate location, the results demonstrate that thermal transmittance has varying impact on the contribution of thermal mass. The locations presenting such behavior were Marseille (−0.99% to +3.89%), Istanbul (−0.73% to +4.21%), Valencia (−1.31% to +4.97%), Algiers (−2.32% to +3.81%), Malaga (−3.95% to +6.21%), Casablanca (−5.66% to +6.96%), and Tel Aviv (−1.81% to +5.44%). These findings demonstrate that the influence of thermal mass is more complex than previously thought and levels should be chosen in relation with the thermal transmittance value.